Factors Associated with Work Stress in Nurses in the Inpatient Room at Sylvani General Hospital, Binjai City in 2023 - Okto Priadi Zega (Journal Health of Indonesian, 2023)
Work stress is a common problem that often occurs or is complained about by workers in various countries. Therefore, this research was conducted with the aim of finding out what factors are related to the incidence of work stress among nurses in the inpatient ward at Sylvani General Hospital, Binjai City in 2023. This research is a quantitative type of research, with a research design using a cross-sectional approach. This research was carried out at the Sylvani General Hospital, Binjai City, with the research time being carried out from February to July 2023. The population in this study was 136 nurses in the inpatient room at Sylvani General Hospital, Binjai City using the Total Sampling technique. Data collection was carried out using a simplified Hurell work stress questionnaire. Data analysis used the chi square test. The research results found were that there was a relationship between the workload variable and work stress with a p-value of 0.026, there was a relationship between the age variable and work stress with a p-value of 0.008, there was a relationship between the work period variable and work stress with a p-value 0.002. The conclusion from this research is that there is a relationship between workload, age and years of work with work stress. Researchers suggest that hospitals implement effective communication regularly before work to clarify roles and responsibilities, carry out analyzes and audits of nursing workforce needs and improve nurses' skills to adapt to developments in the work environment.